C–H⋯F Hydrogen Bond and Integral Intensities of Vinyl C–H Vibtations in Push-Pull β-Dimethylaminotrifluoromethyl Ketone and Its Deuterated Analog. (17th January 2013) - Vdovenko, Sergei; Gerus, Igor; Fedorenko, Elena; Kukhar, Valery
Abstract : The accurate analysis of infrared spectra (both wavenumbers and intensities) of (E)-4-(dimethylamino)-1, 1, 1-trifluorobut-3-en-2-one (DMTBN) and (E)-4-(hexadeutero-dimethylamino)-1, 1, 1-trifluorobut-3-en-2-one (d6 -DMTBN) revealed that besides intramolecular hydrogen bond C – H β ⋯ F – C in the (EE) conformer, these enaminoketones form cyclic dimers between the (EZ) and (EE) conformers due to intermolecular hydrogen bonds, namely, C – H α ⋯ O=C and C – H α ⋯ F – C . Evaluation of constant K H-complex and enthalpy of formation of these H-bonds ( − Δ H ) revealed that C – H α ⋯ O=C bond has greater K H-complex and more negative Δ H than C – H α ⋯ F – C bond (cf. 214.4 M −1, −21.7 kJ M −1 dm 3, and 16.4 M −1, −6.7 kJ M −1 dm 3, resp.). Consequently, stronger H-bond C – H α ⋯ O=C is formed in the first place, whereas weaker H-bond C – H α ⋯ F – C is formed afterward. Moreover, formation of intermolecular C – H α ⋯ F – C hydrogen bond has influence on C–F vibrations, but analysis of this influence must take into account the fact that these vibrations in some cases are coupled with δ CH α . True enthalpy of the equilibrium (EZ) ⇌ (EE) is positive (25.3 kJ M −1 dm 3 ), thus confirming results of DFT calculations, according to which the (EZ) conformer is more stable than the (EE) one.